1998
DOI: 10.1002/(sici)1097-0274(199812)34:6<529::aid-ajim1>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Occupational respiratory allergy in bakery workers: A review of the literature

Abstract: Baker's asthma has long been recognized as a serious disease among workers in the bakery industry and the number of cases with baker's asthma is steadily increasing. This paper presents a review of the available literature on baker's allergy with a special focus on the allergens involved, the epidemiologic research and issues on exposure assessment, evidence of exposure‐response‐relationships, and possible prevention strategies. A large number of potential allergens have been identified and are described here.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
8

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(50 citation statements)
references
References 78 publications
(143 reference statements)
2
40
0
8
Order By: Relevance
“…Exposure to flour and enzymes mainly occurs in bakery workers and grain-processing operators. Flour dust has frequently been associated with occupational asthma in epidemiological studies based on general population samples or asthma registries (Meredith, 1993;Tore´n et al, 1999), and both flour and biological enzymes in studies among bakers (Houba et al, 1998). To date, asthma caused by exposure to mites in the workplace has only been reported for storage mites (Chan-Yeung and Malo, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to flour and enzymes mainly occurs in bakery workers and grain-processing operators. Flour dust has frequently been associated with occupational asthma in epidemiological studies based on general population samples or asthma registries (Meredith, 1993;Tore´n et al, 1999), and both flour and biological enzymes in studies among bakers (Houba et al, 1998). To date, asthma caused by exposure to mites in the workplace has only been reported for storage mites (Chan-Yeung and Malo, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that exposure level is a strong predictor of HMW allergens sensitization [Houba et al, 1998a;Jeffrey et al, 1999;Nieuwenhuijsen et al, 1999Nieuwenhuijsen et al, , 2003. We did, intentionally, not include exposure level in our diagnostic model as we aimed to develop a model consisting of simple questionnaires and laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…Work-related allergic symptoms, for example, asthma, rhinitis, conjunctivitis, and/or eczema are frequently severe enough to produce social and economic consequences at the individual level. A survey in the UK among patients diagnosed with asthma showed that persons with occupational asthma had greater difficulty in finding new jobs, greater loss of income, and were less likely to be currently employed than those with asthma that was unrelated to work [Houba et al, 1998a].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of baker's asthma may develop months or years after first exposure, and risk increases with increasing exposure concentration. In addition to allergy, nonspecific mucous membrane and respiratory irritation also occur frequently among those exposed to flour, possibly more commonly than allergic symptoms [Houba et al 1998b]. …”
Section: Baker's Asthmamentioning
confidence: 99%